The Role of Social Media in Enhancing Online Brand Visibility in B2B Sector on the Example of THT Group - Hołdys, Martyna (Rola mediów społecznościowych w zwiększaniu widoczności marki online w sektorze B2B na przykładzie THT Group, 2025)
The purpose of this paper was to explore the development and implementation of a social media presence for a medium-sized B2B industrial company, with the primary goal of enhancing its online visibility. The study employed market and competitor analysis to identify industry trends and best practices. A strategic approach to content creation and profile development was implemented, followed by monitoring to assess its effects on customer engagement and business growth. The findings highlight the benefits of a strong social media presence, such as increased visibility and improved customer engagement, and also show challenges such as content creation and platform selection. The results confirm the viability of social media for business growth in B2B sector. This research provides a framework for industrial companies to build an effective online presence, contributing new insights into social media strategies in B2B and offering practical guidance for similar firms.
Quote as: Hołdys, M. (2025). The Role of Social Media in Enhancing Online Brand Visibility in B2B Sector on the Example of THT Group. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 94-109). Publishing House of Wroclaw University of Economics and Business.
Keywords: social media strategy; B2B marketing; online visibility; strategia mediów społecznościowych; merketing B2B; widoczność online